Morphological, mechanical, and electromagnetic interference shielding effectiveness characteristics of glass fiber/epoxy resin/MWCNT buckypaper composites - Rojas, Jefersson Alexander; de Paula Santos, Luis Felipe [UNESP]; Botelho, Edson Cocchieri [UNESP]; Ribeiro, Bruno; Rezende, Mirabel Cerqueira (Wiley, 2021)
Glass fiber/epoxy resin composites (GF/EP) using one and three multi-walled carbon nanotube buckypapers (BP) were obtained and their complex parameters, reflectivity, and electromagnetic interference (EMI) shielding effectiveness (SE) at X-band (8.2–12.4 GHz) and Ku-band (12.4–18 GHz) were evaluated. The preparation of BP used polyacrylonitrile (PAN) nanofibers (PF These composites show both large storage and energy loss capacity in both bands revealing promising results related to EMI SE applications. Besides, a high attenuation of around 67% and 72% were achieved for BP based composites. The cross-section view of the buckypaper and the laminates was analyzed by scanning electron microscopy (SEM). The incorporation of the CNT film into the laminates showed no improvements in the elastic properties through dynamic mechanical analyses (DMA). Nevertheless, a decrease in the shear properties by the compression shear test (CST) and interlaminar shear strength (ILSS) has been observed. GF/EP/BP/PF composite presented a reduction of 29 and 39% in its ILSS properties compared to the base laminate (GF/EP). Also, the decrease was even more significant, revealing a steep reduction in its CST properties. On the other hand, the removal of the pan nanofiber (PF) led to better mechanical properties for GF/EP/BP/RPF composites. Results have shown ILSS values of 47.4 ± 2.2 MPa which are close to the base laminate (52.4 ± 3.1 MPa). The removal of the PF provided larger porous in the CNT network, making the impregnation by epoxy easier in the BP/RPF which resulted in improved shear properties compared to GF/EP/BP/PF samples.
Keywords: composites; graphene, and fullerenes; mechanical properties; nanotubes; thermosets